2020
DOI: 10.1097/icl.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Biomarkers for Dry Eye Disease

Abstract: Please confirm the given names (pink) and surnames (blue) of authors have been identified correctly. AU1) Please check and confirm the suggested running head. AU2) Please provide the accessed date for references 7 and 8. AU3) Please note that references "30" and "52" seem to be identical. Hence, reference "52" has been deleted and renumbered accordingly both in the text and in the list to ensure sequential order. Please check and confirm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Several imaging biomarkers are also under study, but require further validation before introduction into a routine clinical setting. 24 Recently, Yang et al reported that lissamine green staining of the conjunctiva correlates with the expression of IFN-γ, IL-6, IL-17, and MMP9 in epithelial cells in patients with dry eye, opening new opportunities in using ocular surface staining to detect inflammation in everyday clinical practice. 25 Such biomarkers may allow identification of patients at greater risk of disease progression, and indicate the most appropriate treatment and management protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Several imaging biomarkers are also under study, but require further validation before introduction into a routine clinical setting. 24 Recently, Yang et al reported that lissamine green staining of the conjunctiva correlates with the expression of IFN-γ, IL-6, IL-17, and MMP9 in epithelial cells in patients with dry eye, opening new opportunities in using ocular surface staining to detect inflammation in everyday clinical practice. 25 Such biomarkers may allow identification of patients at greater risk of disease progression, and indicate the most appropriate treatment and management protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Such composite end points in glaucoma have been demonstrated to increase accuracy of prediction of progression, reduce measurement variability and require smaller sample sizes than single end points derived from, for example, perimetry [22,67]. Similarly, the role of surrogate end points as well as composite end points in clinical studies of dry eye disease is growing [68,69]. Specifically, various clinical scores are used as end points, enabling the development of continuous composite end points [68].…”
Section: Discussionmentioning
confidence: 99%
“…IVCM is a non-invasive imaging modality that enables real-time visualization of the ocular surface tissue and changes in the ocular surface microstructures associated with DED [ 82 , 101 ]. However, although the IVCM image is objective, its interpretation may depend on the subjective assessment of the observers.…”
Section: Application Of Ai In Diagnosis and Treatment Of Dedmentioning
confidence: 99%